The Antibody Germline/Maturation Hypothesis, Elicitation of Broadly Neutralizing Antibodies Against HIV-1 and Cord Blood IgM Repertoires - Prabakaran, Ponraj; Chen, Weizao; Dimitrov, Dimiter S. (Frontiers in Immunology, 2014)
We have previously observed that all known broadly neutralizing antibodies (bnAbs) against HIV-1 are highly divergent from their putative germline predecessors in contrast to bnAbs against henipaviruses and SARS coronavirus, which are much less divergent from their germline counterparts. We have hypothesized that because the germline antibodies are so different compared to the highly somatically mutated HIV-1 bnAbs they may not bind to the Env. This led us to the hypothesis that the immunogenicity of the highly conserved epitopes on the HIV-1 envelope glycoproteins (Envs) is reduced or eliminated by their very weak or absent interactions with germline antibodies. Thus immune responses leading to elicitation of bnAbs may not be initiated and/or sustained; even if they are, the maturation pathways are so complex that prolonged periods of time may be required for elicitation of such bnAbs. In support of the hypothesis, our initial experiments showed that germline-like precursors of several bnAbs do not bind to their epitopes. Recently, a number of research groups working in the HIV vaccine field have obtained data supporting and further expanding the germline/maturation hypothesis. Vaccine immunogens that could bind putative germline antibody predecessors of known bnAbs were successfully generated. However, guiding the immune system through the exceptionally complex antibody maturation pathways in order to elicit those bnAbs remains a major challenge. Here, we summarize developments in the HIV-1 vaccine field based on the germline/maturation hypothesis including our recent data demonstrating germline-like VRC01 antibodies in a human cord blood IgM library.